Vasovagal syncope: asystole provoked by head-up tilt testing under sertraline therapy - Lenk, Mustafa Koray; Alehan, Dursun; Özme, Şencan; Çeliker, Alpay; Özer, Sema (The Turkish Journal of Pediatrics, 1997)
Syncope is defined as a sudden transient loss of consciousness. Vasovagally mediated hypotension and bradycardia are believed common, yet difficult to diagnose, causes of syncope in healthy children and adolescents. These episodes are often both sudden and sporadic in nature and, if recurrent and severe (malignant vasovagal syncope), can be a source of morbidity and possibly mortality. Head-up tilt testing has emerged as a useful investigation in patients who are thought to have recurrent vasovagal syncope with systemic hypotension, bradycardia, or both, and it has been suggested as a potential method to test for vasovagal episodes. Sertraline hydrochloride, a serotonin reuptake inhibitor, has been reported to be effective in preventing the vasovagal syncopal episodes in children and adults. Here, two cases of recurrent, unexplained syncope are presented. Both were under sertraline therapy and underwent provocative head-up tilt testing that resulted in asystole.